Aristotle’s Lost Work On Philosophy - Pacewicz, Artur (Peitho. Examina Antiqua, 2012)
This article offers a Polish translation of Aristotle’s treatise, On Philosophy, of which only certain fragments and testimonies have been preserved. The translation is supplied with an introduction presenting the history of various interpretations and reconstructions of Aristotle’s work.